Sustainable Education Financing in Ukraine: Challenges and Pathways for Local Development - Kulchytska, Nadiia; Bilinchuk, Volodymyr; Mariana Poliak-Sverhun (European Journal of Sustainable Development, 2025)
In modern conditions, solving financial issues in municipal education is an urgent task for state and local governments in Ukraine. In order to achieve this goal, various forms of financial support have been studied, which are conditionally divided into self-financing, household financing, lending and insurance. The author also analyses the economic essence of local budgets, which perform the functions of financial support for local governments, distribution and management of monetary resources. The study’s main results include proposals for an integrated approach to synchronising fiscal mechanisms with educational policy. The internal and external factors influencing the strengthening of the financial base of local self-government are identified, and the principles of budgetary and fiscal mechanisms for the development of the educational environment are outlined. The creation of an effective budgetary mechanism will help to increase the level of socio-economic and educational development of administrative-territorial communities. Keywords: municipal entity, education, financial support of municipal entity, financial support, financial resources.